HISTORY AND FOUNDATION OF THE CONCEPT OF EMOTIONAL INTELLIGENCE - Usarov Jabbor Eshbekovich; Turakulov Bo‘ri Norboevich; Gayupova Saodat (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2020)
The article discusses the history and justification of the concept of emotional intelligence. The article also discusses various topics related to the concept of emotional intelligence, the structure of emotional intelligence, the development of emotional intelligence and personality, the conditions for the development of emotional intelligence, the relationship of general intellectual and emotional intelligence and emotional competence